Factors Affecting Internal Audit Effectiveness in Public Universities: A Systematic Literature Review - Tendai, Muguti Caroline; Matowanyika, Kudzanai; Makurumidze, Shepard (CV. Literasi Indonesia, 2025)
This systematic review examines the critical factors influencing internal audit effectiveness in public universities, a crucial aspect of promoting transparency, accountability, and good governance in higher education institutions. Despite their growing importance, internal audits in these settings face inconsistent effectiveness, with limited empirical consensus on the key determinants of their performance. This study aims to identify, evaluate, and synthesize the existing literature on the factors affecting internal audit effectiveness in public universities. A comprehensive search of academic databases, including Scopus, Web of Science, JSTOR, and Google Scholar, yielded 1,200 records, of which 50 studies were selected for in-depth analysis based on predefined inclusion and exclusion criteria. The findings reveal that internal audit independence, auditor competence, top management support, organizational structure, and coordination with external assurance providers are the most influential factors determining internal audit effectiveness. These factors are crucial in ensuring that internal audits are conducted in a manner that promotes transparency, accountability, and good governance. The study's results have practical implications for policymakers and institutional leaders seeking to strengthen audit practices in public universities. To enhance internal audit effectiveness, institutions should invest in auditor capacity-building, enforce structural independence, and promote integrated audit functions. By prioritizing internal audit effectiveness, institutions can enhance transparency, accountability, and decision-making, ultimately contributing to improved academic outcomes and institutional performance. Future research should focus on regional contextual differences and longitudinal impacts of internal audit reforms to further advance the field. This systematic review provides a foundation for future research and practice in internal audit effectiveness in public universities.